Molecular detection and genomic characterization of diverse hepaciviruses in African rodents. Issue 1 (12th April 2021) - Bletsa, Magda; Vrancken, Bram; Gryseels, Sophie; Boonen, Ine; Fikatas, Antonios; Li, Yiqiao; Laudisoit, Anne; Lequime, Sebastian; Bryja, Josef; Makundi, Rhodes; Meheretu, Yonas; Akaibe, Benjamin Dudu; et al.
Abstract: Hepatitis C virus (HCV; genus Hepacivirus ) represents a major public health problem, infecting about three per cent of the human population. Because no animal reservoir carrying closely related hepaciviruses has been identified, the zoonotic origins of HCV still remain unresolved. Motivated by recent findings of divergent hepaciviruses in rodents and a plausible African origin of HCV genotypes, we have screened a large collection of small mammals samples from seven sub-Saharan African countries. Out of 4, 303 samples screened, eighty were found positive for the presence of hepaciviruses in twenty-nine different host species. We, here, report fifty-six novel genomes that considerably increase the diversity of three divergent rodent hepacivirus lineages. Furthermore, we provide strong evidence for hepacivirus co-infections in rodents, which were exclusively found in four sampled species of brush-furred mice. We also detect evidence of recombination within specific host lineages. Our study expands the available hepacivirus genomic data and contributes insights into the relatively deep evolutionary history of these pathogens in rodents. Overall, our results emphasize the importance of rodents as a potential hepacivirus reservoir and as models for investigating HCV infection dynamics.